(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Performance evaluation is effective and essential to team and individual success. Performance evaluations can increase motivation, working relationships, and the capacity for succession planning when they are conducted well. The study aimed to look into the effectiveness of performance appraisal in motivating employees to attain good performance at Power Tractire Incorporated in Caloocan City. Power Tractire Incorporated (PTTI) is experiencing a situation where there is a disagreement between the management and their employees, causing them to have challenges in delivering employee progress in a performance appraisal that also affects the feedback towards their performance that also results in the lack of enthusiasm at work. Based on the gathered data, the presented factor affecting employee motivation in terms of rewards is "Strongly Agree" if they are fairly compensated for their work, and in terms of Compliments, the achievement of employees are well appreciated and valued by the management is "Agree" while in terms of Work Environment, the job gives the opportunity to learn more skills is "Agree." The Effectiveness of Performance Appraisal in terms of Feedback is well explained and communicated to the employees and interpreted as “Strongly Agree,” while in terms of Progress, gaining new knowledge and skills is also “Strongly Agree,” and in terms of Punctuality, the employee is present at work consistently, understand the value of time, and do work on time without any delays, it is all interpreted as “Strongly Agree,” and the challenges encountered by the employees in dealing with performance appraisal is disagreement against co-workers/management. The researchers recommended that the employees should maintain their current status in the company because it leads to an increased chance of internal promotion and other benefits. It is recommended that the company should focus on fairly compensated for their work in terms of rewards, the achievements of employees are well appreciated and valued by the management, and also the company should focus on job opportunities to learn more skills.